THE EFFECT OF MORINGA OLEIFERA LEAF JUICE FERMENTED BY CELLULOLYTIC PROBIOTIC BACTERIA IN DRINKING WATER ON THE INTERNAL ORGANS OF MALE BALI DUCK - Y. K., Rizki,; Siti, N.W.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika, 2024)
The growth of livestock relies on the function of internal organs such as the heart, liver, gallbladder, pancreas, small intestine, and cecum. One natural element that plays a significant role in the digestive system of ducks is moringa leaves. The beneficial characteristics of moringa leaves (Moringa oleifera) can be enhanced through fermentation using probiotic microorganisms prior to their application as a feed supplement for Bali ducks, as well as for mitigating diseases affecting these birds. This research intends to investigate the potential benefits and drawbacks of consuming Moringa oleifera leaf juice, fermented by cellulolytic probiotic bacteria and incorporated into the drinking water of male Bali ducks to target their internal organs. This research was conducted at the Sesetan Teaching Farm, Faculty of Animal Science, over an 8-week period from December 2023 to February 2024, using a completely randomized design (CRD) comprising 4 treatments and 4 replications, resulting in 16 experimental units. Each unit housed 3 male Bali ducks, totaling 48 ducks. The treatments included: A (no administration of fermented moringa leaf juice in drinking water), B (administration of fermented moringa leaf juice in drinking water at a 2.5% concentration based on body weight), C (administration of fermented moringa leaf juice in drinking water at a 5% concentration based on body weight), and D (administration of fermented moringa leaf juice in drinking water at a 7.5% concentration based on body weight). Observed variables included heart percentage, gallbladder percentage, liver percentage, pancreas percentage, small intestine length, and cecum length. The findings indicate that the administration of fermented moringa leaf juice with cellulolytic probiotic bacteria in drinking water at levels ranging from 2.5% to 7.5% does not significantly affect the internal organs of male Bali ducks.